Online Media Construction in Reporting Rompi Putra Mulyono on detikcom and sindonews.com - Moh Hasbullah; Nur’annafi Farni Syam Maella (Indonesian Journal of Innovation Multidisipliner Research, 2025)
Mass media plays a significant roIe in shaping pubIic opinion by constructing reaIity through news framing. This study aims to analyze how Detik.com and Sindonews.com frame the symbolism of the "Putra Mulyono" vest worn by Kaesang during his public appearances. Using Robert N. Entman's framing model and a qualitative constructivist approach, the study examines news articles and identifies differences in the narratives constructed by the two media outlets. Detik.com tends to present a positive narrative about Kaesang, emphasizing his creativity and humor in responding to criticism. Conversely, Sindonews.com frames the act critically, portraying it as a symbol of the arrogance of the ruling family. These differences highlight how media ideologies influence news narratives, affecting public perceptions and political discourse. The findings underline the importance of media literacy for critically assessing information and understanding the implications of media framing in shaping public opinion.